Environmental awareness and human behavior - Maysaa Younis Ali (Zien Journals, 2023)
The current research aims to identify the concept of environmental awareness, its objectives and aspects, and how to achieve environmental awareness. The awareness of the individual and his behavior in facing the environment and helping social groups and individuals to gain awareness of the environment and its problems. And to identify the most dangerous developments that have affected society in general, those environmental problems that threaten human safety and the safety of the planet on which he lives, and the responsibility to protect the environment is a responsibility shared by individuals, institutions and groups at the formal and informal levels, in order for man to understand and be aware of facts about his environment. He needs someone who educates him to portray it correctly so that this awareness becomes a behavior he follows and a method he follows in his dealings with the components of the environment
Keywords: Environmental awareness; its goals and aspects; individual behavior